¿El juez conoce el Derecho? Algunos aspectos controversiales con relación a la aplicación del principio de iura novit curia en el proceso civil - Prado Bringas, Jorge Rafael (2019)
In this academic work, the authors look into the foundations and limitations of the iura novit curia principle in the Peruvian civil procedure, in order to give practical responses to the main challenges faced by judges in its application. Moreover, they explain that a good understanding of such principle should not permit a judge to submit a judgment based on legal causes that were not duly invoked and defined by the claimant, or that have not been discussed by the parties during the procedure. Finally, they propose that the application of the iura novit curia principle does not allow judges to render a “surprise decision” based on a legal argument that was not part of the controversy in the procedure.